2000
DOI: 10.1164/ajrccm.162.2.9905051
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Chest Wall Mechanics in Anesthetized Children

Abstract: The mechanical behavior of the lung and chest wall has not been determined in preschool children. We therefore obtained static expiratory pressure-volume (P-V) curves of the respiratory system, partitioned into lung and chest wall components using esophageal (Pes) and airway pressure (Paw) registration in 17 anesthetized children (0.2 to 15.5 yr) in the supine and lateral position. From the P-V curves the inspiratory capacity (IC), the chest wall elastance (Ecw), and the maximal compliance of the respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…While static compliance would provide more precise information on respiratory mechanics than the Cdyn measurements we obtained, volume-controlled ventilation is not routinely performed in pediatric anesthetic practice, and more specialized respiratory monitoring equipment is not generally available in clinical practice. 19 The adjustments performed after each surgical intervention to maintain VT/kg also likely had minor (but unmeasured) effects on our results, but these changes were required for clinical care and allowed us to monitor the ventilator adjustments required to maintain control of SpO 2 and EtCO 2 during this type of laparoscopic surgery. Our findings illustrate the effects of this procedure on the parameters available to the anesthesiologist during usual clinical practice, and they illustrate the frequency that ventilation must be adjusted by the anesthesiologist during laparoscopic urological surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While static compliance would provide more precise information on respiratory mechanics than the Cdyn measurements we obtained, volume-controlled ventilation is not routinely performed in pediatric anesthetic practice, and more specialized respiratory monitoring equipment is not generally available in clinical practice. 19 The adjustments performed after each surgical intervention to maintain VT/kg also likely had minor (but unmeasured) effects on our results, but these changes were required for clinical care and allowed us to monitor the ventilator adjustments required to maintain control of SpO 2 and EtCO 2 during this type of laparoscopic surgery. Our findings illustrate the effects of this procedure on the parameters available to the anesthesiologist during usual clinical practice, and they illustrate the frequency that ventilation must be adjusted by the anesthesiologist during laparoscopic urological surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, several studies found no significant differences in oxygenation and respiratory mechanics when comparing pressure vs volume-controlled ventilation during laparoscopic surgery in adults. 18,19 Overall, PCV requires more manipulations than volumecontrolled ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory system compliance (C rs ) may be correlated with height [28, 29, 32], but this relationship is highly non-linear. It may be speculated that if the non-linear relationship between lean body weight and height was of similar nature to the non-linear relationship between respiratory compliance and height, then scaling tidal volumes to lean body mass in pediatric ventilation may indeed minimize volume trauma throughout the height range.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the effects of posture on pulmonary ventilation and perfusion [16][17][18][19][20][21][22], however these studies all gave global measures of the influence of posture and were incapable of providing regional information. Imaging techniques have been explored in recent times to try and overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…For pulmonary physiology in particular, there is a need for non-invasive mapping of the regional distribution of ventilation and perfusion as a function of body orientation and posture [16][17][18][19][20][32][33][34][35]. Additionally, significant questions relating to the care and survival of patients with severe lung diseases such as asthma or acute respiratory distress syndrome relate to postural effects [21,22,36] that an open-access lung MRI could help address.…”
Section: Introductionmentioning
confidence: 99%